1989
DOI: 10.1159/000125303
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Metabolites Modulate Rat Hypothalamic Corticotropin-Releasing Hormone Secretion in vitro

Abstract: Arachidonic acid metabolites have been shown to modulate the secretion of various hormones, including luteinizing hormone, growth hormone and adrenocorticotropin. In this paper we describe the effect of a series of eicosanoids on hypothalamic secretion of corticotropin-releasing hormone (CRH) in vitro. Explanted rat hypothalami in culture were exposed to prostaglandins (PG) F or E2, thromboxane (TX) B2, the TXA2 receptor agonist U-49,619 and leukotrienes (LI) B Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 8 publications
(9 reference statements)
1
31
1
Order By: Relevance
“…CRH secretion has been shown to be modulated in vitro by prostanoids and platelet activating factor, in studies using rat tissues (29)(30)(31). Since the long-term use of NSAIDs by RA patients and NIAIOA controls was comparable in this study, the use of these agents and prostaglandin effects cannot explain the observed hypothalamic defect (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 61%
“…CRH secretion has been shown to be modulated in vitro by prostanoids and platelet activating factor, in studies using rat tissues (29)(30)(31). Since the long-term use of NSAIDs by RA patients and NIAIOA controls was comparable in this study, the use of these agents and prostaglandin effects cannot explain the observed hypothalamic defect (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 61%
“…Prostanoids (prostaglandins and thromboxane A 2 ) generated by several enzymes, including cyclooxygenase, have been demonstrated to act as a neurotransmitter and/or neuromodulator in the brain's actions such as cardiovascular function (Wood et al, 1993;Zhang et al, 2003) and regulation of hormone secretion (Bernardini et al, 1989;Reimsnider and Wood, 2006). Previously, we reported that central pretreatment with indomethacin or ketoprofen (inhibitors of cyclooxygenase) attenuated the centrally administered CRF-, vasopressin-, histamine-, GLP-1-and bombesin-induced elevation of plasma noradrenaline and adrenaline (Okada et al, 2003;Shimizu et al, 2006;Arai et al, 2008;Lu et al, 2008), suggesting the involvement of the brain prostanoids in these substances-induced elevation of plasma catecholamines in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is quite likely that each of these cytokines might initiate a cascade of paracrine and autocrine events with sequential secretion of local mediators of inflammation by nonfenestrated endothelial cells, glial cells, cytokinergic neurons, or all three, resulting in activation of CRH-and AVP-secreting neurons. [112][113] Some of the activating effects of inflammation on the HPA axis may be exerted indirectly through stimulation of the central noradrenergic pathways by the inflammatory cytokines and other humoral mediators of inflammation. Also, activation of peripheral nociceptive, somatosensory, and visceral afferent fibers would lead to stimulation of both the catecholaminergic and the CRH neuronal systems via ascending spinal pathways.…”
Section: Stress System: Immune System Interactions Effects Of the Immmentioning
confidence: 99%
“…Thus, several eicosanoids, platelet-activating factor, and epidermal growth factor have strong CRH-releasing abilities. [112,113,118]It is not clear, however, which of the effects are endocrine and which are paracrine. Direct effects, albeit delayed, of most of these cytokines and mediators of inflammation on pituitary ACTH and adrenocortical glucocorticoid secretion have also been shown.…”
Section: Stress System: Immune System Interactions Effects Of the Immmentioning
confidence: 99%